Forest and Nature Governance A Practice Based Approach - Arts, Bas.; Arts, Bas.; Behagel, Jelle.; Behagel, Jelle.; van Bommel, Séverine.; van Bommel, Séverine.; de Koning, Jessica.; de Koning, Jessica.; Turnhout, Esther.; Turnhout, Esther. (World Forests,, 2013)
Problems such as deforestation, biodiversity loss and illegal logging have provoked various policy responses that are often referred to as forest and nature governance. In its broadest interpretation, governance is about the many ways in which public and private actors from the state, market and/or civil society govern public issues at multiple scales. Examples range from the United Nations’ Convention on Biological Diversity to national forest programmes. In studies of forest and nature governance the dominant approaches are rational choice and neo-institutionalism. This book takes another perspective. Departing from ‘practice theory’, and building upon scholars like Giddens, Bourdieu, Reckwitz, Schatzki and Callon, it seeks to move beyond established understandings of institutions, actors, and knowledge. In so doing, the book not only presents an innovative conceptual and methodological framework for a practice based approach, but also rich case studies and ethnographies. Examples are participatory forest management in the tropics, REDD policy at global level, European water policy, forest certification and the construction of global biodiversity databases. Taking social practices as the key unit of analysis, this book describes how different practitioners, ranging from local forest managers on the ground to policy makers at the global level, work with trees, forests, biodiversity, wildlife, and so on, and act upon forest policies, environmental discourses, codes of conduct, or scientific insights. It is also about how communities, NGOs, stakeholders, and citizens get involved in forest and nature governance.